2008
DOI: 10.1111/j.1399-0039.2008.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the killer cell immunoglobulin‐like receptor gene KIR2DS1 in a Caucasoid Brazilian population with psoriasis vulgaris

Abstract: Psoriasis is a chronic inflammatory skin disease whose pathogenesis and genetic background remain unclear. Considering that previous studies have suggested an association of psoriasis vulgaris (PV) and killer cell immunoglobulin-like receptors (KIRs), we typed 15 KIR genes and human leukocyte antigen (HLA)-Cw in 79 Brazilian Caucasoid patients with PV and 110 healthy controls by polymerase chain reaction (PCR) using sequence-specific oligonucleotides and sequence-specific primers. We did not observe a relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
1
10
2
Order By: Relevance
“…However, in contrast to HLA-Cw*06 , association of KIR2DS1 with psoriasis seemed stronger in higher age at onset values, although the age effect was not significant because of small numbers of patients with late disease onset (Luszczek et al, 2004). Very similar association of KIR2DS1 (and KIR2DL5 in addition, which was not analyzed in our study) was simultaneously published for Japanese population, genetically distant from Poles (Suzuki et al, 2004), and confirmed later in Swedish and Brazilian Caucasians with psoriasis vulgaris (Holm et al, 2005; Jobim et al, 2008), but not in Swedes with guttate psoriasis (Holm et al, 2005) or in Taiwanese Chinese with plaque psoriasis (Chang et al, 2006; see Table 2). Interestingly, KIR2DS1 gene appeared associated also with psoriatic arthritis (Martin et al, 2002b; Holm et al, 2005; Williams et al, 2005; Table 2).…”
Section: Skin Diseases: Psoriasis and Atopic Dermatitissupporting
confidence: 89%
“…However, in contrast to HLA-Cw*06 , association of KIR2DS1 with psoriasis seemed stronger in higher age at onset values, although the age effect was not significant because of small numbers of patients with late disease onset (Luszczek et al, 2004). Very similar association of KIR2DS1 (and KIR2DL5 in addition, which was not analyzed in our study) was simultaneously published for Japanese population, genetically distant from Poles (Suzuki et al, 2004), and confirmed later in Swedish and Brazilian Caucasians with psoriasis vulgaris (Holm et al, 2005; Jobim et al, 2008), but not in Swedes with guttate psoriasis (Holm et al, 2005) or in Taiwanese Chinese with plaque psoriasis (Chang et al, 2006; see Table 2). Interestingly, KIR2DS1 gene appeared associated also with psoriatic arthritis (Martin et al, 2002b; Holm et al, 2005; Williams et al, 2005; Table 2).…”
Section: Skin Diseases: Psoriasis and Atopic Dermatitissupporting
confidence: 89%
“…The results of HLA-C typing were separated into two groups: HLA-C group 1 (C1), consisting of HLA-C 01, 03, 07 (01-06), 08, 12 (02, 03, 06), 14, 16 (01, 03, 04) and HLA-C group 2 (C2) consisting of HLA-C 02, 04, 05, 06, 0707, 12 (04, 05), 15, 1602, 17, 18 [19]. HLA-C group 1 (C1) mol-ecules bind to KIR2DS2, KIR2DL2 and KIR2DL3, while group 2 (C2) molecules bind to KIR2DS1 and KIR2DL1 [20].…”
Section: Hla-c Typingmentioning
confidence: 99%
“…KIR genotypes and HLA ligand patterns have been recognized for diseases and disease conditions such as hepatitis C [18], psoriasis vulgaris [19,20], psoriatic arthritis [21,22], rheumatoid arthritis [23], celiac disease [24], ulcerative colitis [25,26], Crohn's disease [27], human immunodeficiency virus [28], recurrent miscarriage [29], and leprosy [30], as well as in T1D [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%